What Is Complex/Emotional About Emotional Complexity? - Berrios, Raul (Frontiers in Psychology, 2019)
Affective experiences can fluctuate, be combined, and fused, resulting in various phenomena labeled as emotional complexity. Despite the lack of a common theoretical framework, several phenomena including mixed emotions, emodiversity, meta-emotions, awe, among several others, have been defined as emotional complexity. In this conceptual analysis, I aim to integrate the diversity of emotional complexity by describing various phenomena associated with this construct. This integration offers a more comprehensive panorama of the current usage of the concept of emotional complexity compared to previous attempts to consolidate the field. Furthermore, this conceptual analysis intends to disentangle the emotional fingerprints of emotional complexity. In particular, I present evidence and arguments showing that complex emotions can be characterized as having specific facial expressions, appraisals, and functional significance. Finally, I suggest that it is possible to describe emotional complexity using concepts and properties from the complex systems theory. Concepts such as the hierarchical organization of the affect system and emergent self-organization are used to explain current evidence on emotional complexity. I explain that applying complex systems theory to emotional complexity is not only theoretically convenient, but that complex systems theory also serves to advance new forms to conceptualize the affect system. The current conceptual analysis can help to organize current research and theory in order to encourage new research endeavors in the field of emotional complexity and acknowledge the importance of emotional complexity in models of affect, for which I suggest some specific guidelines.